2018
DOI: 10.1186/s13063-018-2933-8
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive aids for people with early stage dementia versus treatment as usual (Dementia Early Stage Cognitive Aids New Trial (DESCANT)): study protocol for a randomised controlled trial

Abstract: BackgroundThere is a growing need for an evidence-based approach to home support for people with dementia and their carers following diagnosis but research on the effectiveness and cost-effectiveness of different approaches is sparse. The Dementia Early Stage Cognitive Aids New Trial (DESCANT) will evaluate the clinical and cost-effectiveness of a range of memory aids, training and support to people with mild to moderate dementia and their carers at home and compares that intervention with treatment as usual.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…We published the trial protocol in Trials in 2018. 151 This included the sample size estimation for the primary outcome of the ADL for people with dementia, as measured by the Bristol Activities of Daily Living Scale (BADLS), 152 and a description of the intervention and of all trial procedures. The methods of the trial and findings on clinical effectiveness are summarised below.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We published the trial protocol in Trials in 2018. 151 This included the sample size estimation for the primary outcome of the ADL for people with dementia, as measured by the Bristol Activities of Daily Living Scale (BADLS), 152 and a description of the intervention and of all trial procedures. The methods of the trial and findings on clinical effectiveness are summarised below.…”
Section: Discussionmentioning
confidence: 99%
“…Cost-effectiveness analysis followed an agreed statistical analysis plan, which was summarised in the trial protocol paper in Trials in 2018. 151 The aim was to evaluate whether or not DSPs with guidance in using memory aids were cost-effective compared with TAU for a range of values of willingness to pay (WTP) for a QALY gained. The perspective of the primary analysis was public (NHS and social care), carer (costs) and people with dementia and their carer (health benefits), but multiple perspectives were also presented (see Appendix 11).…”
Section: Early-stage Dementia: Within-trial Economic Analysismentioning
confidence: 99%
“…This paper considers the experience of people with dementia taking part in a pragmatic RCT investigating the effectiveness and cost-effectiveness of providing a range of memory aids, training and support to people with mild to moderate dementia and their carers at home (Chester et al, 2018). The trial forms part of a wider research programme, Effective Home Support in Dementia Care: Components, Impacts and Costs of Tertiary Prevention, comprising nine interrelated projects funded through a National Institute for Health Research (NIHR) programme grant for applied research.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study is threefold to: investigate the goals identified by people with dementia and their carers to promote the self‐management of symptoms and abilities; measure achievement using the goal attainment process; and explore the reflections of Dementia Support Practitioners (DSPs) facilitating it. This was part of the Dementia Early Stage Cognitive Aids New Trial (DESCANT) trial described in detail elsewhere 29 . An overview is provided below.…”
Section: Methodsmentioning
confidence: 99%
“…Ethical approval was obtained from the National Research Ethics Service (NRES) (15/NW/0822). The effectiveness and cost‐effectiveness of the intervention was assessed through a randomised controlled trial 29 ; and its implementation by process evaluation 30 . A specially convened subgroup, including an experienced occupational therapist, oversaw the process evaluation and the development, implementation and reporting of this GAS.…”
Section: Methodsmentioning
confidence: 99%